OPTIMALISASI DISTRIBUSI DANA SOSIAL ISLAM MELALUI PERBANKAN SYARIAH - Roifatus Syauqoti; Aip Wahidzul Latif; Luluk Wahyu Roficoh (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Islamic banks are intermediary institutions that perform two functions, namely commercial and social functions. However, the social function of Islamic banks has not been fully realized in practice and the real sector, as banks tend to focus more on business and financial performance while neglecting social aspects. As Sharia-compliant financial institutions, Islamic banks have a Islamic Social Finance function, the have authority to collect zakat, infaq, sadaqah, grants, and other social funds and distribute them to the relevant institutions. This study employs a qualitative approach through a literature review and analyzes the data using deductive reasoning to draw conclusions. The findings indicate that the distribution of zakat has not been optimal due to the commingling of zakat funds with infaq and sadaqah funds, all of which are collectively recognized as part of Corporate Social Responsibility (CSR) programs. Existing zakat distribution practices are more focused on productive distribution schemes that generate long-term impacts, while the fulfillment of basic needs, which is a prerequisite for productive zakat, has not been adequately addressed. From an institutional perspective, there is also a lack of coordination and cooperation between Islamic banks and the National Zakat Agency (BAZNAS). The distribution of zakat can be optimized through the separation of zakat funds from CSR funds, as well as the separation of zakat from infaq and sadaqah funds. Furthermore, a proper classification of mustahik (zakat beneficiaries) is needed to ensure that both consumptive and productive zakat distributions are appropriately targeted. Enhanced coordination and collaboration between Islamic banks and BAZNAS are also essential to improve the effectiveness of zakat distribution.